Diseño de un terminal terrestre para la ciudad de Cayambe - Manosalvas Solano, Edwin Javier (2024)
The canton of Cayambe is located in the Andes Mountains, northeast of the province of Pichincha, 52 km from Quito, the capital of Ecuador. Located on the slopes of the snowy Cayambe, it is a unique and charming natural destination, internationally recognized for its blanket of snow that blends with the sky, attracting thousands of tourists looking for a unique experience at 4,740 meters above sea level. Additionally, Cayambe is home to 41% of the paramos and is part of the Cayambe-Coca National Park, which is part of the National System of Protected Areas and presents an excellent opportunity for tourism. In recent years, the canton has experienced notable growth, which has generated mobility prblems in urban transport and the frequency of trips within and outside the canton. For this reason, it is crucial to design an interprovincial land transportation terminal in the city that responds to the current and future needs of the canton. An analysis of the Cayambe canton, based on surveys, opinions of passers-by and urban studies, has shown that the current municipal land terminal does not meet the necessary conditions due to space limitations and a design that has been gradually modified since its creation. For this reason, Cayambe needs a new infrastructure that provides adequate spaces for the better development of its activities. The Municipal GAD, in its development and territorial planning plan, has planned the construction of a new land terminal, although it still does not have the architectural-urban project. This project will cover an area of 45,780 m² and will be located on a land of 68,310 m². It is proposed to design a modern, functional, clean, efficient and orderly land terminal, prioritizing user comfort and complying with all municipal architecture and urban planning standards. The project will be developed on two floors, with public, semi-public and private areas, distributed in three zones: administrative, exchange and distribution, and complementary services. The construction will use a mixed system of metal structure and concrete. The land terminal will serve 105,781 inhabitants and will have boarding and disembarkation platforms, administrative offices, commercial premises and rest areas for drivers.